2000
DOI: 10.1097/00004647-200008000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of the VIP1 Receptor (VPAC1R) in Rat Cerebral Blood Vessels: Relation to PACAP and VIP Containing Nerves

Abstract: The two structurally related peptides, vasoactive intestinal polypeptide (VIP) and pituitary adenylate cyclase activating polypeptide (PACAP), are present in cerebral vascular nerve fibers. Biologic actions of VIP are exerted through two receptors, VPAC1 and VPAC2, having similar binding affinity for both VIP and PACAP. In the current study, the authors have developed a specific antibody against the rVPAC1 receptor to examine the localization of rVPAC1 immunoreactivity in cerebral arteries and arterioles of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 31 publications
2
66
3
Order By: Relevance
“…The VPAC 1 agonist induces NO-and endothelial-dependent vasodilation over the same concentration range as VIP, which is in agreement with the immunocytochemical findings that this receptor is located on the endothelium. This is in contrast to a previous study, which identified VPAC 1 receptors on vascular smooth muscle cells of rat superficial cerebral arteries (Fahrenkrug et al, 2000). This highlights a possible species difference or a difference between the distributions of the VPAC 1 receptor in basilar and superficial cerebral arteries (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…The VPAC 1 agonist induces NO-and endothelial-dependent vasodilation over the same concentration range as VIP, which is in agreement with the immunocytochemical findings that this receptor is located on the endothelium. This is in contrast to a previous study, which identified VPAC 1 receptors on vascular smooth muscle cells of rat superficial cerebral arteries (Fahrenkrug et al, 2000). This highlights a possible species difference or a difference between the distributions of the VPAC 1 receptor in basilar and superficial cerebral arteries (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Particularly, mRNAs for VPAC1 receptors that are reputed to mediate dilatation in pial arteries (Yaksh et al, 1987;Fahrenkrug et al, 2000), were expressed in smooth muscle cells of intracortical microvessels, and VIP elicited a potent dilatation in these microvessels. In contrast, the failure of CCK to alter microvascular tone correlated well with the lack of CCK receptor expression in microvascular smooth muscle, suggesting that this peptide is unlikely to directly couple flow to neuronal activity.…”
Section: Vasoactive Mediatorsmentioning
confidence: 99%
“…In previous studies (Amenta et al 1991 ;Fahrenkrug et al 2000 ;Erdling et al 2013 ), the vascular effects of PACAP1-38 were investigated in segments of rat middle cerebral artery (MCA) by pressurized arteriography and in a wire myograph. The authors have found the same magnitude of concentration-dependent relaxations of the MCA, in arteries of rat dura, whereas in human meningeal arteries, PACAP1-38 induced weak relaxations (Arsalan et al 2013;Baun et al 2011 ).…”
Section: Pacap-induced Relaxations Of Basilar Arteriesmentioning
confidence: 99%
“…The vascular actions of PACAP1-38 are more effective compared to those of PACAP1-27 (Huang et al 1992 ;Okazaki et al 1992 ). The vasodilator activity of PACAP has been documented in vessels of various organs (Nandha et al 1991 ;Ross-Ascuitto et al 1993 ) via three specific receptors (PAC1R and VPAC1R/VPAC2R), both of which are highly expressed in the cerebral and peripheral blood vessels (Fahrenkrug et al 2000 ;Nandha et al 1991 ). They are localized in the smooth muscle cells of cerebral arteries and arterioles (Fahrenkrug et al 2000 ;Amenta et al 1991 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation